Recent Insights into Insulin-Like Growth Factor Binding Protein 2 Transcriptional Regulation - Shin, Minsang (Endocrinol Metab (Seoul), 2017)
Insulin-like growth factor binding proteins (IGFBPs) are major regulators of insulin-like growth factor bioavailability and activity in metabolic signaling. Seven IGFBP family isoforms have been identified. Recent studies have shown that IGFBPs play a pivotal role in metabolic signaling and disease, including the pathogenesis of obesity, diabetes, and cancer. Although many studies have documented the various roles played by IGFBPs, transcriptional regulation of IGFBPs is not well understood. In this review, we focus on the regulatory mechanisms of IGFBP gene expression, and we summarize the findings of transcription factor activity in the IGFBP promoter region.